Selective DMSO-induced conformational changes in proteins from Raman optical activity - Batista, Andrea N. L. [UNESP]; Batista, Joao M. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Blanch, Ewan W. (Royal Soc Chemistry, 2013)
The function of a protein is determined by its structure, which is intrinsically related to its solvent environment. Based on this paradigm, there has been a great deal of interest in the role that nonaqueous solvents play in regulating protein structure, with some debate in the literature regarding dimethyl sulfoxide (DMSO). Thus, in this work we have used Raman and Raman optical activity (ROA) spectroscopies to investigate conclusively the changes induced by DMSO in the secondary structure of an array of proteins including human serum albumin (highly alpha-helical), bovine alpha-lactalbumin (mainly alpha-helical), bovine ribonuclease A (containing both alpha-helix and beta-sheet), bovine beta-lactoglobulin (mainly beta-sheet), and bovine alpha-casein (disordered). Our results clearly demonstrate that 100% DMSO solutions destabilize alpha-helices completely, converting them into the poly(L-proline) II (PPII) helix conformation. However, low concentrations of DMSO (10% v/v) were found to have little effect on the structure of even the most helical protein, human serum albumin. In the case of alpha-casein, the natively unfolded protein rich in PPII helix was converted into a further disordered structure when dissolved in pure DMSO. By contrast, beta-sheets remained mostly unaffected regardless of DMSO concentration. While providing new insights into protein structure in organic solvents, this work reinforces the capability of vibrational optical activity to assess conformations of biomolecules in conditions not accessible to other techniques, such as X-ray crystallography and NMR.